An evaluation of teaching ESP reading strategies for electrical engineering third-year students at Hanoi university of Industry : Đánh giá các kỹ thuật giảng dạy kỹ năng đọc hiểu tiếng Anh chuyên ngành cho sinh viên năm thứ 3 khoa điện ở trường Đại học Cô - Nguyễn, Thị Thanh Hằng (University of Languages and International Studies, 2017)
Hanoi University of Industry (hereafter HaUI) is known as a multidisciplinary school which has contributed significantly to the training of the technical labor force for the development of the Vietnamese industry. Hence, along with general English-training courses, English for Specific Purposes (hereafter ESP) courses that has attracted much attention from students at this university. For ESP-training context at HaUI, though ESP reading strategies have long been implemented and applied in its programs, nevertheless, up to now, there is no in-depth study to assess the effectiveness of the ESP reading strategies yet. Therefore, this study is carried out to evaluate theteaching ESP reading strategiethat is being applied for Electrical Engineering third-year students at Hanoi University of Industry to offer recommendations for the purpose of improving the teaching ESP reading strategies in a more efficient way. The participants selected for thestudy included 95 Electrical Engineering third-year students and 4 ESP lecturers at HaUI. The results from the survey questionnaires for students and lecturers investigate ESP reading strategies currently employed by the English teachers and find out appropriate teaching strategies to contribute more highly teaching quality of lecturers in ESP reading lessons at HaUI. Recommendationsand suggestions for further researches are given in order to enhance more effectiveness in teaching ESP reading strategies.